2009
DOI: 10.1016/j.cpc.2008.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional lattice polymers: Adaptive windows simulations

Abstract: We report a numerical study of self-avoiding polymers on the square lattice, including an attractive potential between nonconsecutive monomers. Using Wang-Landau sampling (WLS) with adaptive windows, we obtain the density of states for chains of up to N = 300 monomers and associated thermodynamic quantities. The method enables one to simulate accurately the lowtemperature regime, which is virtually inaccessible using traditional methods. Instead of defining fixed energy windows, as in usual WLS, this method us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…As a new application of the criterion, we consider a homopolymer consisting of N monomers which may assume any self avoiding walk (SAW) configuration on a two-dimensional lattice [19,20]. Assuming that the polymer is in a bad solvent, there is an effective monomermonomer attraction in addition to the self-avoidance constraint representing excluded volume.…”
Section: Homopolymermentioning
confidence: 99%
“…As a new application of the criterion, we consider a homopolymer consisting of N monomers which may assume any self avoiding walk (SAW) configuration on a two-dimensional lattice [19,20]. Assuming that the polymer is in a bad solvent, there is an effective monomermonomer attraction in addition to the self-avoidance constraint representing excluded volume.…”
Section: Homopolymermentioning
confidence: 99%
“…On the other hand, Schulz et al [12] found it advantageous to introduce an additional rule, namely, whenever a configuration is rejected because its energy is greater than the maximum value, E > , of a given window, one should update g(E) for the current energy value. These prescriptions are effective for Ising models but do not eliminate boundary effects in all instances, e.g., in simulations of polymers [13] and systems where the JDOS is required [14].…”
mentioning
confidence: 99%
“…These difficulties have been overcome by the development of alternative MC methods, such as paralleltempering [16], cluster algorithms [17], multicanonical algorithms [18], and more recently the Wang-Landau method [19]. This method has been applied with great success to many systems, in particular to polymers in lattice [20][21][22].…”
Section: Introductionmentioning
confidence: 98%